The risk factors and interventions of dental caries in the elderly: a narrative review / Eleena Mohd Yusof ... [et al.] - Mohd Yusof, Eleena; Ismail, Ikmal Hisham; Abdul Rahim, Aini Hayati; Mohamed Zohdi, Noorharliana; Jaapar, Mustaffa; Ahmad, Rohana (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
As the human lifespan increases, older adults are known to retain their teeth for longer. Dental clinicians will see an increase in the number of elderly patients as the population's life expectancy rises. The loss of periodontal attachment is a common risk factor for root surface caries development in older adults. Other risk factors include an increase in the number of missing teeth and restorations, prosthesis wearing, reduced manual dexterity, a shift in diet from complex to simple sugars, salivary gland dysfunction and increased salivary glucose levels. Dental caries is one of the causes leading to tooth loss in older adults and tooth loss significantly impacts the oral health-related quality of life for this vulnerable age group. Furthermore, the treatment of root caries is complicated by the adhesion of restorative materials to dentin and cemental layer. To curb these issues, understanding the risk factors for dental caries in the elderly, as well as its prevention and treatment strategies, is therefore crucial. This narrative review aims to provide an understanding of dental caries in older adults and an evidence-based prevention and management of this dental disease.